2023
DOI: 10.1097/pr9.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postoperative pain after hospital discharge: systematic review and meta-analysis

Abstract: Supplemental Digital Content is Available in the Text. This systematic review of 27 studies estimated the prevalence of moderate-to-severe pain after hospital discharge to be from 31% to 58%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Early adverse effects associated with poor functional analgesia include cardiorespiratory complications including atelectasis, hypoxia, and pulmonary infection [1][2][3], while poorly managed pain may precipitate the onset of neuropathic pain post thoracotomy [4,5]. Although the development of various complications after all neuraxial blocks were extensively studied during the last decades [6][7][8][9][10], the development of post thoracotomy chronic pain remains an issue resulting in patient suffering, increased health resource utilization, and persistent post-operative opioid use (PPOU) [11]. Post-thoracotomy pain syndrome (PTPS) is a well-investigated medical entity with nearly a 10% of the patients affected developing life-changing chronic pain issues [12].…”
Section: Introductionmentioning
confidence: 99%
“…Early adverse effects associated with poor functional analgesia include cardiorespiratory complications including atelectasis, hypoxia, and pulmonary infection [1][2][3], while poorly managed pain may precipitate the onset of neuropathic pain post thoracotomy [4,5]. Although the development of various complications after all neuraxial blocks were extensively studied during the last decades [6][7][8][9][10], the development of post thoracotomy chronic pain remains an issue resulting in patient suffering, increased health resource utilization, and persistent post-operative opioid use (PPOU) [11]. Post-thoracotomy pain syndrome (PTPS) is a well-investigated medical entity with nearly a 10% of the patients affected developing life-changing chronic pain issues [12].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of postoperative pain may be a bit higher than we thought. A recent meta-analysis showed that the incidence of moderate to severe postoperative pain in discharged patients ranged from 31% one day after discharge to 58% one to two weeks after discharge [ 6 ]. Therefore, perioperative pain management is still one of the main concerns of anesthesiologists.…”
Section: Introductionmentioning
confidence: 99%